Gastrointestinal Tract Disorders - Durazzo, Marilena (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Gastrointestinal tract disorders are a wide group of diseases involving both the gastrointestinal tube (esophagus, stomach, small and large intestine) and related organs (liver, pancreas, and gallbladder). These dysfunctions may differ by site, etiology, and severity, going from simple malfunctions to mere diseases. Because of their variety and heterogeneity, gastrointestinal disorders can affect many people and are widespread throughout the population. Therefore, scientific research in this area is facing a great challenge. Better knowledge of gastrointestinal disorders in terms of their pathophysiology, clinical features, and possible complications is necessary for the development of new diagnostic methods and therapeutic strategies. During the last several decades, some scientific developments have already been made, giving more opportunities to these patients. However, much remains to be discovered and to be done to help physicians in their everyday work and to give patients a better prognosis. The present Special Issue aims to highlight recent advances in gastrointestinal tract disorders, focusing on their diagnostic and therapeutic path, evolution, and complications.